Second Language Learning via Syntactic Priming: Investigating the Role of Modality, Attention, and Motivation. Issue 1 (10th October 2022) - Coumel, Marion; Ushioda, Ema; Messenger, Katherine
Abstract: We examined whether input modality and individual differences in attention and motivation influence second language (L2) learning via syntactic priming. In an online study, we compared the primed production of English passives by 235 L2 and native English speakers in reading‐to‐writing versus listening‐to‐writing conditions. We measured immediate priming (producing passives immediately after exposure to passives) and short‐ and long‐term learning (producing more passives in immediate and 1‐week delayed posttests relative to pretests). Both groups showed immediate priming and short‐ and long‐term learning, although L2 speakers produced more passives with immediate priming and showed greater long‐term learning. Learning was unaffected by modality, but immediate priming was greatest in the listening‐to‐writing condition across groups. Individual differences in attention and motivation did not influence priming or learning. Thus, syntactic priming fosters long‐term L2 learning regardless of input modality, but participants may be sensitive to the frequency of passives in spoken versus written language during immediate priming. Abstract : A one‐page Accessible Summary of this article in non‐technical language is freely available in the Supporting Information online and at https://oasis‐database.org